The role of personality traits in web based education - (:unkn) unknown (TURKISH ONLINE JOURNAL EDUCATIONAL TECH-TOJET, 2008)
This study aims to investigate the relationships among personality traits and learners' academic achievement in a web based environment and attitudes towards web based education. 127 students enrolled in the e-MBA Masters Degree of Bilgi University constituted the study group of the research. A survey method was used for the study and the data were collected by Web Based Education Attitudes Scale and The Adjective Check List (ACL). At the end of the study, it was revealed that the students were successful in the web based education environment with the average of 3.091 out of 4.00. The average of students' attitudes towards web based education was 97.212 out of 135. The arithmetical average of the items in the attitudes scale was 3.738 out of 5.00. Also, significant relationships were found between learners' personality traits, academic achievement and attitudes towards web based education. The findings revealed that personality traits explain about 53.2% of the academic achievement, and 52.7% of the attitudes towards web based education.
Keywords: web based education; personality traits; academic achievement; attitudes towards web based education; STUDENTS